Suicide in Sociological Perspective: From Classical, Modern to Postmodern Views - Alimin Alwi (Cita konsultindo, 2025)
Suicide is a psychological issue that affects individuals, but it also represents complicated societal dynamics and integration issues in contemporary society, which makes this research significant. This study's goal is to examine the phenomena of suicide from a sociological standpoint, drawing on Emile Durkheim's classical ideas as well as contemporary sociological theories including conflict theory, symbolic interactionism, and critical sociology. The methodology is qualitative library research using a variety of primary and secondary materials from national and international books and scientific journals. According to the study's findings, societal factors that greatly influence suicidal behavior include social stigma, structural inequity, inadequate social cohesion, and the pressures of consumerist culture and social media. In conclusion, a sociological perspective offers a more thorough comprehension of suicide as a social occurrence, indicating that preventative tactics ought to concentrate on societal structural and cultural shifts in addition to focusing on people.